The Surgical Approach to the Anterior Nucleus of Thalamus in Patients With Refractory Epilepsy: Experience from the International Multicenter Registry (MORE). Issue 1 (15th March 2018) - Lehtimäki, Kai; Coenen, Volker A; Gonçalves Ferreira, Antonio; Boon, Paul; Elger, Christian; Taylor, Rod S; Ryvlin, Philippe; Gil-Nagel, Antonio; Gielen, Frans; Brionne, Thomas C; Abouihia, Abdallah; Beth, Grégory; et al.
Abstract: BACKGROUND: The Medtronic Registry for Epilepsy (MORE; Medtronic Inc, Dublin, Ireland) is an open label observational study evaluating the long-term effectiveness, safety, and performance of deep brain stimulation (DBS) of the anterior nucleus of thalamus (ANT) for the treatment of refractory epilepsy. OBJECTIVE: To compare the difference in success rate of placing contacts at ANT-target region (ANT-TR) between transventricular (TV) and extraventricular (EV) lead trajectories in 73 ANT-DBS implants in 17 European centers participating in the MORE registry. METHODS: The success rate of placing contacts at ANT-TR was evaluated using a screening method combining both individual patient imaging information and stereotactic atlas information to identify contacts at ANT-TR. RESULTS: EV lead trajectory was used in 53% of the trajectories. Approximately, 90% of the TV lead trajectories had at least 1 contact at ANT-TR, vs only 71% of the EV lead trajectories. The success rate for placing at least 1 contact at ANT-TR bilaterally was 84% for TV implants and 58% for EV implants ( P < .05; Fisher's exact). No intracranial bleedings were observed, but 1 cortical infarct was reported following EV lead trajectory. CONCLUSION: The results of this registry support the use of TV lead trajectories for ANT-DBS as they have a higher probability in placing contacts at ANT-TR, without appearing to compromise procedural safety. Follow-up data collection is continuing in the MORE registry. These data will provide outcomes associated with TV and EV trajectories.